Synthesis and Characterization of Barium Titanate and Barium Indate-Zirconate Perovskite Oxyhydrides - Johansson, Isac (My University, 2025)
The global imperative to reduce CO2 emissions has driven interest in catalytic conversion technologies, particularly CO2 hydrogenation, which transforms CO2 into valuable chemicals. This reaction often relies on metallic nanoparticles supported on catalyst substrates, commonly metal oxides like Al2O3 or ZrO2. Perovskite oxides have emerged as promising alternatives due to their adjustable surface chemistry, thermal stability, and ability to host redox-active defect sites. Recent attention has turned to anion-adjusted perovskite materials, amongst them oxyhydrides, where oxygen anions are partially replaced by hydride ions. These modifications can enhance catalytic performance and introduce properties such as hydride ion conductivity and interesting electronic and magnetic properties. This project focused on the synthesis and structural analysis of reduced perovskite oxides of synthesised barium titanate (BaTiO3), nano-crystalline barium titanate and barium indate-zirconate (BaZr1−xInxO3− x2 ). For BaTiO3, synthesis routes mainly investigated reduction with CaH2 enclosed in stainless steel capsules, filled with high purity argon. For BaZr1−xInxO3− x2 , reduction by H2 gas annealing was investigated. Characterization heavily relied on powder X-ray diffraction (PXRD) and thermogravimetric analysis (TGA) measurements. Inelastic neutron scatterin (INS) was performed for a reduced 50% indium substituted BaZr0.5In0.5O2.75. The study primarily investigated how synthesis parameters such as molar ratio of CaH2, temperature, and heating time affect reduction extent, anion composition, phase formation, impurity formation and crystallinity. The CaH2 reduction of synthesized tetragonal BaTiO3 at 600◦C for 48 hours yields reduced products with a cubic phase, accompanied by a colour change from white to dark blue or black. An increased molar ratio of CaH2 leads to a greater degree of reduction. Rietveld refinements indicate formation of a single phase in these reduced samples. In contrast, samples of nano-BaTiO3 subjected to the same reduction conditions exhibit a lower degree of reduction and show more pronounced two-phase indications. Higher molar CaH2 ratios result in the formation of Ba2TiO4 impurities. These impurity phases can be reduced by decreasing the CaH2 ratio. For the nano-BaTiO3, a temperature decrease to 580◦ C doesn’t impact Ba2TiO4 amounts. Shortening the heating time to 24 hours leads to decreased amounts, at the expense of a lower reduction extent in the nano-BaTiO3 perovskite phase. Hydrogen annealing of BaZr1−xInxO3− x2 with 50% indium substitution at 800◦ C for 24 hours and 70% substitution at 650◦ C for 20 hours give reduced perovskite oxides of barium indate-zirconate. The extent of reduction is comparable between the two compositions. Inelastic neutron scattering (INS) measurements on the 50% BaZr1−xInxO3−x/2 sample indicate minimal hydride incorporation.